FOREIGN LANGUAGE COMMUNICATIVE COMPETENCE AS AN IMPORTANT INDICATOR OF PROFESSIONALISM FOREIGN LANGUAGE TEACHER IN PRIMARY SCHOOL - Shatalova, S.V. (Pedagogy of Higher and Secondary Education, 2022)
The article reveals some prior directions as for investigating foreign language communication competence as a particular feature of primary school teacher professional skills.